2022
DOI: 10.3389/fncel.2022.820127
|View full text |Cite
|
Sign up to set email alerts
|

Protein Expression of the Microglial Marker Tmem119 Decreases in Association With Morphological Changes and Location in a Mouse Model of Traumatic Brain Injury

Abstract: The activation of microglia and the infiltration of macrophages are hallmarks of neuroinflammation after acute brain injuries, including traumatic brain injury (TBI). The two myeloid populations share many features in the post-injury inflammatory response, thus, being antigenically indistinguishable. Recently Tmem119, a type I transmembrane protein specifically expressed by microglia under physiological conditions, was proposed as a tool to differentiate resident microglia from blood-borne macrophages, not exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 66 publications
2
25
0
Order By: Relevance
“…This suggests that TMEM119 protein is likely still involved in the activation of microglia, although the process of its downregulation in reactive microglia remains unclear. The present data in TBI ( Mercurio et al, 2022 ) are in agreement with the findings in the brain of patients with Alzheimer’s disease, in which the TMEM119 immunoreactivity is greatly reduced in the amyloid plaque-surrounding microglia and is often associated with a significant increase in Iba1 reactivity ( Swanson et al, 2020 ; Kenkhuis et al, 2022 ; Vankriekelsvenne et al, 2022 ). Moreover, the downregulation of TMEM119 protein in the contused area is in line with the findings at the sites of neurodegeneration where TMEM119 immunoreactivity is reduced in the disease-associated microglia ( Krasemann et al, 2017 ; Deczkowska et al, 2018 ; Satoh et al, 2019 ).…”
supporting
confidence: 91%
See 3 more Smart Citations
“…This suggests that TMEM119 protein is likely still involved in the activation of microglia, although the process of its downregulation in reactive microglia remains unclear. The present data in TBI ( Mercurio et al, 2022 ) are in agreement with the findings in the brain of patients with Alzheimer’s disease, in which the TMEM119 immunoreactivity is greatly reduced in the amyloid plaque-surrounding microglia and is often associated with a significant increase in Iba1 reactivity ( Swanson et al, 2020 ; Kenkhuis et al, 2022 ; Vankriekelsvenne et al, 2022 ). Moreover, the downregulation of TMEM119 protein in the contused area is in line with the findings at the sites of neurodegeneration where TMEM119 immunoreactivity is reduced in the disease-associated microglia ( Krasemann et al, 2017 ; Deczkowska et al, 2018 ; Satoh et al, 2019 ).…”
supporting
confidence: 91%
“… Mercurio et al (2022) reported an upregulation of Tmem119 gene expression in frozen brain sections of TBI (Day 7) by RT-PCR and using in situ hybridization experiments; they further confirmed its upregulation, specifically in the contused area and surrounding regions, along with increased microglial activation. These findings are consistent with a study showing the increased Tmem119 mRNA level in frozen tissue of the frontal cortex from patients with Alzheimer’s ( Satoh et al, 2016 ), which suggests that increased Tmem119 gene expression in the whole population of microglia is paralleled with tissue inflammation.…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…Furthermore, when the CNS is confronted with pathological conditions such as neurodegenerative diseases or ischemic stroke, the deleterious circumstance can enhance the combination of the complement fragment C1q and synapses, which causes the over-activation of microglial phagocytosis towards synapses and eventually damages the neuronal cells ( Mercurio et al, 2022 ). Dying neurons undergo p53-mediated apoptotic signaling pathway, which leads to the expression of the downstream target gene Dkk1 and further inactivates the Wnt/β-catenin signaling pathway ( Wang et al, 2000 ).…”
Section: Implications Of Wnt/β-catenin Signaling Pathway Within Neura...mentioning
confidence: 99%